Platform Online Dalam Perkuliahan Pada Masa Pandemi Covid-19 - Dewi Surani; Jaka Wijaya Kusuma; Nugrahini Kusumawati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: During the Covid-19 pandemic, lecturers and students were forced to adapt to the online lecture process by utilizing various online platforms. The purpose of this study is to explore the use of online platforms in online lectures during the Covid 19 pandemic, its strengths and weaknesses, constraints and solutions. The data were collected using a survey method by giving a questionnaire to 64 lecturer participants from all over Indonesia who were randomly selected. The results showed that lecturers were more likely to use familiar, familiar and easy-to-use platforms such as WhatsApp, followed by other platforms such as Zoom, Google Classroom while still carrying out technical implementation such as face-to-face learning such as lecture schedules on schedule, attendance attendance, fixed material referring to the RPS, evaluation of material with varied assignments and still seeking solutions to existing problems or constraints. The advantages of using online platforms include supporting the delivery of material in an attractive manner, smooth interaction, while the disadvantages are less interactive, less fluent lecture communication and tends to be one-way, wasteful of quotas, inadequate internet access, less than optimal understanding of material, and level of participation. low student. The use of online platforms in lectures during the Covid-19 pandemic requires both infrastructure and non-structural readiness to optimize the online lecture process during the Covid-19 pandemic.Abstrak: Pada masa pandemi Covid-19 dosen dan mahasiswa dipaksa untuk beradaptasi dengan proses perkuliahan online dengan memanfaatkan berbagai platform online. Tujuan penelitian ini mengeksplorasi pemanfaatan platform online di perkuliahan online pada masa pandemi covid 19, kelebihan dan kekurangnya, kendala serta solusinya. Data diambil dengan metode survei dengan memberikan angket kuesioner kepada 64 partisipan dosen di seluruh wilayah Indonesia yang dipilih secara acak. Hasil penelitian menunjukan bahwa dosen lebih cenderung menggunakan paltform yang sudah familiar dikenal dan mudah digunakan seperti WhatsApp, diikuti platform lainnya, seperti  Zoom, Google Classroom dengan tetap melakukan teknis pelaksanaan seperti dalam pembelajaran tatap muka seperti jadwal pelaksanan perkuliahan sesuai jadwal, adanya absensi kehadiran, materi tetap mengacu ke RPS, evaluasi materi dengan penugasan yang variatif dan tetap mengupayakan solusi terhadap masalah atau kendala yang ada. Kelebihan pemanfaatan platform online, yaitu mendukung penyampaian materi dengan menarik, interaksi yang lancar, sementara kekurangannya ialah kurang interaktif, komunikasi perkuliahan kurang lancar dan cenderung satu arah, boros kuota, akses internet yang kurang memadai, pemahaman materi yang kurang maksimal, dan tingkat partisipasi mahasiswa yang rendah. Pemanfaatan platform online dalam perkuliahan di masa pandemi Covid-19 membutuhkan kesiapan baik infrastruktur maupun nonstruktur guna mengoptimalkan proses perkuliahan online selama pandemi Covid-19.